Salvaging collateral damage by COVID-19 pandemic in form of exposed silicone ear framework in 33-year post reconstructed ear - Tiwari, Vinay Kumar; Nanda, Deepak; Tandon, Raman; Mula, Rohit Babu (International Journal of Research in Medical Sciences, 2021)
Total ear reconstruction is being practiced by different techniques. Ready to use Silicone ear framework (Silastic ear framework by Dow corning) was being used frequently by Plastic surgeons in the eighties and nineties of the twentieth century. Framework exposure, either due to skin necrosis or due to infection used to be the commonest complication in the early postoperative period. A follow-up case of a 50 year old male patient, our 33 years follow up case of Total ear reconstruction by silicone ear framework implantation presented to us with exposed silicone framework and infection. Due to constant use of facemask with elastic ear loop for support during COVID-19 pandemic. The exposed infected implant successfully salvaged using negative pressure wound therapy. In all cases of autologous or alloplastic ear reconstruction, we strictly recommend not to use facemasks with elastic ear loops. If a facemask has to be used it should have a head loop or to be used with an ear protector.